2018
DOI: 10.1002/hbm.23953
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of activation patterns preceding hallucinations in patients with schizophrenia using machine learning with structured sparsity

Abstract: Despite significant progress in the field, the detection of fMRI signal changes during hallucinatory events remains difficult and time-consuming. This article first proposes a machine-learning algorithm to automatically identify resting-state fMRI periods that precede hallucinations versus periods that do not. When applied to whole-brain fMRI data, state-of-the-art classification methods, such as support vector machines (SVM), yield dense solutions that are difficult to interpret. We proposed to extend the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…It has been demonstrated that this classifier generates a coherent, parsimonious and interpretable predictive map: a highly desirable characteristic in the scope of predictive signature discovery. For example, Enet‐TV has been successfully used, recently, in the prediction of prehallucination functional MRI patterns in a clinical population of schizophrenia patients .…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that this classifier generates a coherent, parsimonious and interpretable predictive map: a highly desirable characteristic in the scope of predictive signature discovery. For example, Enet‐TV has been successfully used, recently, in the prediction of prehallucination functional MRI patterns in a clinical population of schizophrenia patients .…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, because half of the sample did not reach the threshold for a positive response to chemo-facilitated psychotherapy, we expect our findings to also be relevant for future neuromodulation trials for severely impaired PTSD patients. In this vein, a recent study confirmed that such patients could be trained to downregulate amygdalar activity using real time fMRI-based neurofeedback (66).…”
Section: Discussionmentioning
confidence: 87%
“…This appears compatible with prior hypotheses of inner speech as a form of action (35). In contrast, hippocampal or temporoparietal structures, also known to be involved in AVH pathophysiology (6,3638), possibly by reflecting the spatiotemporal, rich and complex content of these experiences (21,39), were not necessary to reach high decoding performances. Even if anteroposterior dysconnectivity between speech-related areas has been regularly shown to be involved in AVHs (40), this new finding suggests either that (a) the highly variable nature of the information computed by these temporal-hippocampal structures is not stereotyped enough to be decoded using lSVM or (b) that most of the fine-grained relevant information conserved between subjects is encoded in Broca’s BOLD activity.…”
Section: Discussionmentioning
confidence: 91%